Analisis Manajemen Risiko Usaha Beras dan Penggilingan JN - Rafli Renaldi, Rafli Renaldi; Rahmawati, Repa; Marsella, Anggun; Ferdian, Adam Devan (Universitas Serambi Mekkah, 2024)
Rice milling businesses are a vital pillar in supporting food security in Indonesia, especially considering that rice is the staple food for the majority of the population. However, this sector faces numerous challenges that threaten its operational and financial sustainability, including market price fluctuations, dependency on harvest yields, technological limitations, and legal issues. If not properly managed, these risks can reduce the efficiency, quality, and competitiveness of the business. This study aims to develop an integrated risk management strategy for rice milling businesses by identifying and analyzing various types of risks they face. Through the SWOT analysis approach and risk matrix, this project provides a comprehensive overview of the strengths, weaknesses, opportunities, and threats within business operations. The study also evaluates risks based on their probability of occurrence and level of impact, covering six main categories: market risks, financial risks, marketing risks, operational risks, human resource risks, and legal risks. The analysis reveals that market risks, such as price fluctuations and dependency on seasonal harvests, have a high probability and significant impact. Operational risks, such as equipment breakdowns, also represent critical factors affecting productivity. In addition, financial risks, including unstable cash flow and limited capital, pose significant threats to business continuity. To address these issues, the study proposes mitigation strategies such as product diversification, technological modernization, human resource optimization, and strengthening financial management. The study concludes that a structured risk management approach can help rice milling businesses improve operational efficiency, financial stability, and overall sustainability amid increasing market competition. The recommended mitigation strategies are expected to enhance the competitiveness and resilience of the business against various uncertainties in the future. Thus, this business model not only ensures survival but also supports growth as an integral part of the national food system.